E-Book Development of Trading Company Adjustment Journal Based on 2013 Curriculum - Krisnaresanti, Aldila; Slamet, Achmad; Wahyudin, Agus (Journal of Economic Education, 2018)
The establishment of 2013 Curriculum had not been counter balanced with the supply of textbook that has been customized to 2013 Curriculum. This research was an e-book development research on trade company adjustment journal based on 2013 Curriculum with the purposes : 1) To analyze the use of e-book on trade company accounting subject especially on the matter of trade company adjustment journal that has been execute so far; 2) To analyze the development design of trade company adjustment journal based on 2013 Curriculum; and 3) To analyze feasibility of the e-book of trade company adjustment journal that has been developed. This research was a research and development research that was executed in two phases, prfeliminary study phase and developmental phase. Result obtained in preliminary study was that the teacher on accounting skill subject had not use the e-book on the learning process of trade company accounting subject, especially on the matter of adjustment journal. E-book development design was started with the planning, early product design, assessment from material and media experts., revision, teacher assessment, revision, and student assessment. Result from student assessment regarding trade company adjustment journal e-book based on 2013 Curriculum yields 87,42% and categorized as good which means it is feasible to be used as media in the learning process.